1993
DOI: 10.1104/pp.103.1.267
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Signals from Avocado Surface Wax Trigger Germination and Appressorium Formation in Colletotrichum gloeosporioides

Abstract: l h e surface wax of the host, avocado (Persea americana) fruit, induced germination and appressorium formation in the spores of Colletotrichum gloeosporioides. Waxes from nonhost plants did not induce appressorium formation in this fungus, and avocado wax did not induce appressorium formation in most Colletotrichum species that infect other hosts. Bioassays of the thin-layer chromatographic fractions of the avocado wax showed that the fatty alcohol fraction was the main appressorium-inducing component. Testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0
6

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(124 citation statements)
references
References 4 publications
(5 reference statements)
4
114
0
6
Order By: Relevance
“…The cuticle permeability modification in these transgenic plants could be responsible for a less efficient perception of the fungal elicitors, delaying the activation of the defense responses. Furthermore, it has been shown that leaf or fruit waxes could contain active components that induce germination and appressorium formation by fungal pathogens (Podila et al, 1993;Hegde and Kolattukudy, 1997;Reisige et al, 2006). Therefore, VLC alkanes accumulated on the CER1ox leaf surface could act as components activating the development of the fungus or could deeply perturb the hydrophobic properties of the leaf cuticle and allow better fungus propagation.…”
Section: Role Of Wax Vlc Alkanes In Biotic Stress Responsementioning
confidence: 99%
“…The cuticle permeability modification in these transgenic plants could be responsible for a less efficient perception of the fungal elicitors, delaying the activation of the defense responses. Furthermore, it has been shown that leaf or fruit waxes could contain active components that induce germination and appressorium formation by fungal pathogens (Podila et al, 1993;Hegde and Kolattukudy, 1997;Reisige et al, 2006). Therefore, VLC alkanes accumulated on the CER1ox leaf surface could act as components activating the development of the fungus or could deeply perturb the hydrophobic properties of the leaf cuticle and allow better fungus propagation.…”
Section: Role Of Wax Vlc Alkanes In Biotic Stress Responsementioning
confidence: 99%
“…They act as substrates for the attachment of colonizing organisms to the leaf surface (Clement et al, 1994;Tucker and Talbot, 2001), and they also play crucial roles in plant-pathogen and plant-pest signaling (Kolattukudy et al, 1995;Chassot and Métraux, 2005;Reina-Pinto and Yephremov, 2009). It is well established that some wax components, such as triterpenoids and aldehydes, are important in pre-invasion processes, including spore germination and appressorium formation, in different plant species (Podila et al, 1993;Gniwotta et al, 2005;Reisige et al, 2006;Inada and Savory, 2011). Inada and Savory (Inada and Savory, 2011) recently demonstrated in Arabidopsis that pre-penetration processes in the biotrophic fungus Golovinomyces orontii were suppressed on cauline leaves, stems, siliques and roots compared to rosette leaves.…”
Section: Cuticular Waxes and Biotic Interactionsmentioning
confidence: 99%
“…Little is known about cuticular functions with regard to saprophytic microbial life on leaf surfaces. Interactions between the cuticle and micro-organisms are pertinent during cellular adhesion (Young & Kauss, 1984 ;Kuo & Hoch, 1996), growth and reproduction, differentiation processes (Uchiyama & Okuyama, 1990 ;Podila, Rogers & Kolattukudy, 1993 ;D. Knoll and L. Schreiber Flaishman, Hwang & Kolattukudy, 1995) and metabolic activities of micro-organisms that eventually influence cutin and wax composition.…”
Section: mentioning
confidence: 99%